The Visual Guide to Morality: Vision as an Integrative Analogy for Moral Experience, Variability and Mechanism. Issue 4 (April 2016) - Schein, Chelsea; Hester, Neil; Gray, Kurt
Abstract: Analogies help organize, communicate and reveal scientific phenomena. Vision may be the best analogy for understanding moral judgment. Although moral psychology has long noted similarities between seeing and judging, we systematically review the "morality is like vision" analogy through three elements: experience, variability and mechanism. Both vision and morality are experienced as automatic, durable and objective. However, despite feelings of objectivity, both vision and morality show substantial variability across biology, culture and situation. The paradox of objective experience and cultural subjectivity is best understood through constructionism, as both vision and morality involve the flexible combination of more basic ingredients. Specifically, both vision and morality involve a mechanism that demonstrates Gestalt, combination and coherence. The "morality is like vision" analogy not only provides intuitive organization and compelling communication for moral psychology but also speaks to debates in the field, such as intuition versus reason, pluralism versus universalism and modularity versus constructionism.